Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1111/j.1600-0447.1976.tb00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen (Lioresal®) in the treatment of neuroleptic‐induced tardive dyskinesia

Abstract: A double-blind cross-over trial of the effects of baclofen and placebo was carried out in 20 female patients suffering from neuroleptic-induced tardive dyskinesia. After 14 days of treatment 15 patients showed improvement of baclofen, whereas none showed improvement on placebo; baclofen was thus significantly more effective than placebo. Baclofen is a GABA-like drug which passes through the blood-brain barrier and which reduces the neuroleptic-induced increase of dopamine turn-over. In tardive dyskinesia is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(15 citation statements)
references
References 12 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…It is uncertain, however, whether this effect is exerted through GABA synapses (Davies and Watkins, 1974;Anden and Wachtel, 1977), or occurs as a direct effect on dopamine receptors. On the assumption that baclofen is a GABA agonist, it has been used to treat the chorea of Huntington's disease (Barbeau, 1973), tardive dyskinesias (Korsgaard, 1976), and schizophrenia (Frederiksen, 1975;Bigelow et al, 1977), and has been shown to aggravate neuroleptic-induced Parkinsonism (Gerlach, 1977). As a result of a previous report in which a patient with idiopathic Parkinson's disease on levodopa developed visual hallucinations, abnormal involuntary movements, and reduced levodopa tolerance after the abrupt withdrawal of baclofen (Lees et al, 1977a), the effect of baclofen on levodopatreated Parkinsonism has been investigated.…”
Section: Baclofen (8-parachlorophenyl Gammabutyric Acid)mentioning
confidence: 99%
“…It is uncertain, however, whether this effect is exerted through GABA synapses (Davies and Watkins, 1974;Anden and Wachtel, 1977), or occurs as a direct effect on dopamine receptors. On the assumption that baclofen is a GABA agonist, it has been used to treat the chorea of Huntington's disease (Barbeau, 1973), tardive dyskinesias (Korsgaard, 1976), and schizophrenia (Frederiksen, 1975;Bigelow et al, 1977), and has been shown to aggravate neuroleptic-induced Parkinsonism (Gerlach, 1977). As a result of a previous report in which a patient with idiopathic Parkinson's disease on levodopa developed visual hallucinations, abnormal involuntary movements, and reduced levodopa tolerance after the abrupt withdrawal of baclofen (Lees et al, 1977a), the effect of baclofen on levodopatreated Parkinsonism has been investigated.…”
Section: Baclofen (8-parachlorophenyl Gammabutyric Acid)mentioning
confidence: 99%
“…Another interesting development in the same sphere is the use of baclofen, a GABA-like drug which passes through the blood brain barrier in the treatment of drug-induced TD. In a double-blind, placebo-controlled, cross over clinical trial with 20 female drug-in duced TD patients, baclofen was found to be beneficial in 15 patients while the placebo was not useful in any [104], However, the effectiveness of the drug may not be attribut able to enhancing GABA but may be related to its ability to decrease dopamine turnover [105]. Perhaps the potential therapeutic ef fects of these drugs can only act as catalysts for further research.…”
Section: Gamma Aminobutyric Acidmentioning
confidence: 99%
“…1975;Korsgaard, 1976;Bigelow et al, 1977;Nair et al, 1980]. This drug has been postulated to exert its effects by acting as a GABA agonist inhibiting dopamine transmission [Anden, 1977], as an antagonist of substance P [Saito et al, 1975] and more recently as a phenyl ethylamine agonist , This report describes our clinical experience with ba clofen in subjects with prominent features of tardive dys kinesia and in chronic schizophrenic patients.…”
Section: Introductionmentioning
confidence: 99%